NHC in Imidazolium Acetate Ionic Liquids: Actual or Potential Presence? - Chiarotto, Isabella; Mattiello, Leonardo; Pandolfi, Fabiana; Rocco, Daniele; Feroci, Marta (Frontiers in Chemistry, 2018)
Ionic liquids (ILs) are considered in the majority of cases green solvents, due to their virtually null vapour pressure and to the easiness in recycling them. In particular, imidazolium ILs are widely used in many fields of Chemistry, as solvents or precursors of N-heterocyclic carbenes (NHCs). The latter are easily obtained by deprotonation of the C2-H, usually using strong bases or cathodic reduction. Nevertheless, it is known that weaker bases (e.g., triethylamine) are able to promote C2-H/D exchange. From this perspective, the possibility of deprotonating C2-H group of an imidazolium cation by means of a basic counter-ion was seriously considered and led to the synthesis of imidazolium ILs spontaneously containing NHCs. The most famous of this class of ILs are N,N'-disubstituted imidazolium acetates. Due to the particular reactivity of this kind of ILs, they were appointed as "organocatalytic ionic liquids" or "proto-carbenes". Many papers report the use of these imidazolium acetates in organocatalytic reactions (i.e., catalysed by NHC) or in stoichiometric NHC reactions (e.g., with elemental sulfur to yield the corresponding imidazole-2-thiones). Nevertheless, the actual presence of NHC in N,N'-disubstituted imidazolium acetate is still controversial. Moreover, theoretical studies seem to rule out the presence of NHC in such a polar environment as an IL. Aim of this Mini Review is to give the reader an up-to-date overview on the actual or potential presence of NHC in such an "organocatalytic ionic liquid", both from the experimental and theoretical point of view, without the intent to be exhaustive on N,N'-disubstituted imidazolium acetate applications.